Urban weather data to estimate reference evapotranspiration for rural irrigation management - Luo, Y.; Jiang, Y.; Peng, S.; Khan, S.; Xueliang Cai; Wang, W.; Jiao, X. (American Society of Civil Engineers, 2012)
Weather data measured in urban areas are generally more easily available than those in rural areas. If the urban weather data are used to calculate the reference crop evapotranspiration (ET0) for rural irrigation management or spatial and temporal trend analysis, the results may be biased because of the differences in weather variables. We collected daily data for mean, maximum, and minimum temperatures; relative humidity; average wind speed; and sunshine duration from two stations: Kaifeng Station in the City of Kaifeng and Huibei Station in the nearby irrigation scheme for 1984-2009. ET0 for both stations were calculated using the FAO-56 Penman-Monteith method and then compared. The results indicated that the difference in daily ET0 was remarkable [with relative error (RE) of 52.6%], the difference between monthly average ET0 increased gradually during the last three decades and the temporal trends in annual average daily ET0 were opposite. There were significant differences in ETC (with RE of 31.1%) and irrigation requirements (with RE of 24.3%) between the two stations. Even though the distance between the two stations is only 20 km, the urban weather cannot be used to estimate ET0 for rural irrigation management.